2021
DOI: 10.5603/jtm.2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glues — the current state of knowledge

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Studies evaluating the use of fibrin-based adjuncts have reported >80% success rates at achieving hemostasis on raw liver surfaces and have been found to be effective in patients with underlying coagulopathies 19,35,36 . Unfortunately, fibrin-based sealants typically require specialized equipment for deployment and require special storage considerations 37 . They are also expensive to produce, and some carry a tangible risk for viral transmission or allergic reactions ranging from skin reactions to anaphylaxis 37,38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating the use of fibrin-based adjuncts have reported >80% success rates at achieving hemostasis on raw liver surfaces and have been found to be effective in patients with underlying coagulopathies 19,35,36 . Unfortunately, fibrin-based sealants typically require specialized equipment for deployment and require special storage considerations 37 . They are also expensive to produce, and some carry a tangible risk for viral transmission or allergic reactions ranging from skin reactions to anaphylaxis 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…19,35,36 Unfortunately, fibrin-based sealants typically require specialized equipment for deployment and require special storage considerations. 37 They are also expensive to produce, and some carry a tangible risk for viral transmission or allergic reactions ranging from skin reactions to anaphylaxis. 37,38 The two-ply pectin patches used in this study are stored at room temperature and are easy to apply without the need for specialized equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advantages of autologous products, commercial fibrin glue has become the most popular fibrin glue since it became available on the market in 1998. Pharmaceutical companies such as Tisseel from Baxter Healthcare produce commercial fibrin glue as a surgical additive [ 26 ]. It is produced and supplied in separate vials with a dual syringe delivery system, in which human-plasma-derived thrombin containing ionic calcium and a fibrinogen-containing anticoagulant are first separated into two vials.…”
Section: Evolution Of Platelet-rich Derivativesmentioning
confidence: 99%
“…Klej fibrynowy stosuje się również w chirurgii ogólnej, stomatologii, chirurgii sercowo-naczyniowej, okulistycznej, torakochirurgii, neurochirurgii, laryngologii, ginekologii czy urologii, zwłaszcza u pacjentów z zaburzeniami krzepnięcia. [13] Powszechnie stosowaną grupą produktów uzyskiwanych z osocza są immunoglobuliny podawane domięśniowo (IMIG). Wśród dostępnych preparatów znajdziemy m.in.…”
Section: Przykłady Zastosowań Produktów Medycznych Uzyskanych Z Osoczaunclassified